Brain morphometric abnormalities and their associations with affective symptoms in males with methamphetamine use disorder during abstinence - Hu, Xinyue; Jiang, Ping; Gao, Yingxue; Sun, Jiayu; Zhou, Xiaobo; Zhang, Lianqing; Qiu, Hui; Li, Hailong; Cao, Lingxiao; Liu, Jing; Gong, Qiyong; Huang, Xiaoqi (Frontiers in Psychiatry, 2022)
Background: Methamphetamine (METH) use induces neurotoxic effects in brain structures and affective symptoms that persist during abstinence. However, the brain morphometry of individuals with METH use disorder (MUD) remain unclear, as well as their associations with affective symptoms during abstinence. Methods: Forty-eight abstinent males with MUD and 66 age-, sex- and education-matched healthy controls (HCs) underwent high-resolution T1-weighted magnetic resonance imaging. Cortical thickness, surface area, volume, local gyrification index (LGI), and subcortical volume were obtained with FreeSurfer software. Brain morphometry differences between groups and their associations with affective symptoms and drug abuse history within the males with MUD were examined, with intracranial volume, age and years of education as covariates. Results: Compared with the HCs, the individuals with MUD showed a significantly higher LGI in the right cuneus gyrus, left lingual gyrus, bilateral supramarginal gyrus, right inferior parietal gyrus (IPG), and right dorsal anterior cingulate cortex (clusterwise p<0.05, Monte Carlo-corrected), as well as a smaller volume of the left nucleus accumbens (NAcc) (p<0.05, FDR-corrected). However, there were no significant group differences in cortical thickness, area or volume. In addition, the LGI in the right IPG was positively associated with the severity of depression and anxiety symptoms in MUDs (p<0.05, FDR-corrected). Conclusion: Brain morphometric abnormalities in abstinent males with MUD were characterized by hypergyrification across multiple mid-posterior brain regions and a smaller volume of the left NAcc. Gyrification of the right IPG may be a potential neural substrate underlying the affective symptoms experienced by MUDs during abstinence.